A combined first-principles computational/experimental study on LiNi 0.66Co 0.17Mn 0.17O 2 as a potential layered cathode material - Saavedra-Arias, José (2012)
First-principles calculations are used to analyze the phase stability, formation energy, and Li intercalation potential for a series of layered cathode materials. The calculations show LiNi 0.66Co 0.17Mn 0.17O 2 as a promising cathode for lithium-ion batteries. The layer-structured LiNi 0.66Co 0.17Mn 0.17O 2 is prepared via wet chemical route, followed by annealing at 1123 K and characterized using powder X-ray diffraction, scanning electron microscopy, and X-ray photoelectron spectroscopy. The characterization techniques reveal single-phase LiNi 0.66Co 0.17Mn 0.17O 2 with highly ordered structure. Galvanostatic charge-discharge curves recorded at 1C show the discharge capacity of ca. 167 mAh g -1 and good cyclic performance for 25 cycles.